UPAYA PENINGKATAN INTERAKSI DAN AKTIVITAS BELAJAR DALAM PEMBELAJARAN KOSAKATA DENGAN STRATEGI ANALISIS FITUR SEMANTIK - Kusmiatun, Ari (LITERA, 2005)
This study is aimed at improving the process of learning Indonesian, especially the vocabulary, by means of the feature analysis strategy as an appropriate strategy to make students active and interactive in the learning process so that their vocabulary mastery and, in turn, their communicative competence can improve. The subjects of the study were the second year students of Marketing Study Program, Vocational High School Abdi Negara Muntilan, Magelang. The steps in the study included problem identification, research design making, action, observation, and reflection. All were carried out in three cycles, each of which consisted of three actions. The research data were both quantitative and qualitative. All participants were involved in the data analysis to meet the criteria of data suitability comprising the democratic, process, and dialogic validity. The research findings show that the feature analysis strategy in the vocabulary learning can improve (1) students' activity, 2) their interaction, and 3) their vocabulary mastery. The various activities and the optimum interaction among students prove that their communicative competence is better. Key words: feature analysis strategy, vocabulary, activities, interaction